2003
DOI: 10.1101/gad.1125903
|View full text |Cite
|
Sign up to set email alerts
|

Ku interacts with telomerase RNA to promote telomere addition at native and broken chromosome ends

Abstract: Ku is a conserved DNA end-binding protein that plays various roles at different kinds of DNA ends. At telomeres, Ku is part of the structure that protects the chromosome end, whereas at broken DNA ends, Ku promotes DNA repair as part of the nonhomologous end-joining (NHEJ) pathway. Here, we present evidence of a new role for Ku that impacts both telomere-length maintenance and DNA repair in Saccharomyces cerevisiae. We show that Ku binds TLC1, the RNA component of telomerase. We also describe a novel separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
345
1
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(356 citation statements)
references
References 54 publications
9
345
1
1
Order By: Relevance
“…14 A second pathway for telomerase recruitment also exists which involves interactions between TLC1, Est1/Est2/Est3 and the Ku70/80 heterodimer. 15,16 This latter mechanism study from Kramer and Haber demonstrated that de novo telomere formation is an extremely rare event at a persistent, HO-induced DSB. 41 In contrast, de novo telomere formation becomes efficient if a tract of 81 telomeric TG [1][2][3] repeats is inserted adjacent to the HO recognition site.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…14 A second pathway for telomerase recruitment also exists which involves interactions between TLC1, Est1/Est2/Est3 and the Ku70/80 heterodimer. 15,16 This latter mechanism study from Kramer and Haber demonstrated that de novo telomere formation is an extremely rare event at a persistent, HO-induced DSB. 41 In contrast, de novo telomere formation becomes efficient if a tract of 81 telomeric TG [1][2][3] repeats is inserted adjacent to the HO recognition site.…”
Section: Introductionmentioning
confidence: 97%
“…28 appears to play a key role in de novo telomere formation at DSBs that lack extensive TG repeats. 16,17 Persistent DSBs are Targeted to the Nuclear Periphery How does the cell respond when a DSB remains un-repaired for a long period of time? In yeast, cells can eventually inactivate the cell cycle checkpoint response (a process termed checkpoint adaptation) and proceed through mitosis with a broken chromosome, but adaptation occurs only after ∼15 hours of failed DSB repair.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that telomerase is transiently expressed in S-phase in some normal human cells, yet fails to maintain overall telomere length, but protect karyotypic stability by "capping"chromosome ends and by resetting chromatin during DNA replication [42] without adding telomeric repeats. An earlier report indicated that intrachromosomal DNA breaks are occasionally repaired by healing with telomeric DNA repeat sequences [43], suggesting that telomerase may participate in DNA repair. In addition, hTERT has been found to be associated with DNA replication protein primase [44].…”
Section: Telomerase In Dna Damage Responsesmentioning
confidence: 99%